Notes on village systems of small ruminant production in Ghana and a bibliography of Ghanian small ruminant research - Asare, E.O.; Wilson, R.T. (International Livestock Centre for Africa, 1985)
Reports partial results of a study of small ruminant production in nine villages in the Kumasi area of Ghana. Describes the management systems and outlines flock demography.